Current Status of Health and Social Services for Children with Autism in Iran: Parents’ Perspectives - Hadi Zarafshan; Mohammad Reza Mohammadi; Farid Abolhassani; Seyed Abbas Motevalian; Neda Sepasi; Vandad Sharifi (Iranian Journal of Psychiatry, 2018)
Objective: The present study is a part of a larger study that aimed at developing a comprehensive model of service delivery for individuals with autism in Iran based on the local needs and characteristics. In this study, the status of the services provided to those with autism in Iran was investigated based on the perspectives of parents of children with autism.